2020
DOI: 10.1101/2020.05.25.111351
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Convergent and distributed effects of the schizophrenia-associated 3q29 deletion on the human neural transcriptome

Abstract: The 1.6Mb 3q29 deletion (3q29Del) confers >40-fold increased risk for schizophrenia (SZ) and is also a risk factor for intellectual disability (ID) and autism spectrum disorders (ASD). No single gene in this interval is definitively associated with SZ, ID, or ASD, prompting the hypothesis that neurodevelopmental sequelae emerge upon loss of multiple functionally-connected genes. However, 3q29 interval genes are unevenly annotated and the impact of the 3q29Del on the human neural transcriptome is not known. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 131 publications
1
2
0
Order By: Relevance
“…The present study was the first to identify metabolic deficits in the context of the 3q29 deletion. Furthermore, we found pervasive sex-specific effects of the 3q29 deletion; these findings are supported by transcriptome network analysis by our team that identified a module enriched for estrogen-related signaling (Sefik et al, 2020). These results have important implications, both for the 3q29 deletion specifically and for metabolic and mechanistic studies more generally.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The present study was the first to identify metabolic deficits in the context of the 3q29 deletion. Furthermore, we found pervasive sex-specific effects of the 3q29 deletion; these findings are supported by transcriptome network analysis by our team that identified a module enriched for estrogen-related signaling (Sefik et al, 2020). These results have important implications, both for the 3q29 deletion specifically and for metabolic and mechanistic studies more generally.…”
Section: Discussionsupporting
confidence: 74%
“…Data from animal models have revealed pervasive roles for estrogen and estrogen-related signaling in metabolic processes including fat metabolism and storage (Faulds et al, 2012). An independent study by our group using transcriptome network analysis identified a co-expression module significantly enriched for estrogen-dependent signaling (p=5.08E-06) that contained the 3q29 deletion interval gene PAK2 (Sefik et al, 2020). Together with the existing literature on sex differences in fat metabolism and our finding that male and female B6.Del16 +/ Bdh1-Tfrc mice are differentially affected by 3q29 deletion-associated metabolic phenotypes, this finding suggests that sex is an important consideration in defining the biological mechanisms underscoring phenotypes in 3q29del.…”
Section: Discussionmentioning
confidence: 99%
“…The association that we identified between cerebellar cortex volume and positive symptom severity in 3q29Del may help elucidate one part of this question, as this finding suggests that one or more genes affected by the hemizygous deletion of the 3q29 interval modulate the link between cerebellar development and psychosis-risk. In fact, many genes located in this interval, including DLG1 and BDH1, which have been proposed as drivers of neuropsychiatric phenotypes (133,134), show medium-high expression in the cerebellum (https://www.proteinatlas.org/). Its protracted development may increase the cerebellum's susceptibility to perturbations of these genes (135,136).…”
Section: Discussionmentioning
confidence: 99%